Use of medicinal plants for the treatment of cervical diseases - Aliaga Salguero , Javier Juan (2024)
Objective: Determine the use of medicinal plants in cervical diseases in women who attend the Huancán health center. Material and Methods: The present research was qualitative-quantitative since it allowed us to identify traditional practices which have been used for many years, especially in our region; of qualitative ethnographic design since it allowed us to analyze the knowledge of these medicinal plants used to treat cervical pathologies in such a way that it was possible to understand these homeopathic practices that are usually carried out by the immigrant populations of Ayacucho and Huancavelica settled in our district of Huancán. Results: Existence of cervical diseases, 51.8% (124) mentioned having one of these diseases, and 48.2% (117) mentioned not having it. Regarding the knowledge that cervical diseases were known, 44.8% (108) reported HPV infection, 38.2% (92) reported sexually transmitted infections-STIs and only 5.4% (13) reported knowing. to chronic cervicitis as a cervical disease. In the same way, regarding the use of medicinal plants in the treatment of cervical infections, chamomile shows 53.1% (128) as the main plant expressed by the respondents; of which 29.9% (70) reported using ovules as an adjuvant to their treatment. Finally, in the evaluation of the results of the use of medicinal plants, 57.7% (139) mentioned having considerable improvements Conclusions: The use of medicinal plants influences the treatment of cervical diseases.